MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MELALUI PEMBELAJARAN PROBLEM CREATING MATERI PERBANDINGAN SISWA KELAS VII SMP NEGERI 3 TULUNGAGUNG - Endro Purwanto (STKIP PGRI TULUNGAGUNG, 2015)
Based on the preliminary observation in SMPN 3 Tulungagung, have been obtained if there were no special efforts to increase the ability of problem solving through the Problem CreatingLearning on the students. This research was a class-action research which collaboratively conducted between the researcher as a teacher and mathematic teachers and peers as observers. The research subject was the students of VII,9 which amount 29 students. The data has been collected by (1) the learning process, (2) observation of the students’ activities during the learning process, (3) observation of the teachers’ activities during the Problem Creating-Learning, (4) Analysis of Students work based on the answers of the Students Worksheet, (5) Achievement test. On the problem creating-learning, in order to increase the ability of problem solving on the students, the researcher suggests to the teachers to : allocate the time carefully in designing the lesson plan and managing the learning process, to arrange, to supervise and to lead the students so they would optimally do the team work.